Non-state actors in Malaysia’s migration management: privatisation and the rise of immigration contractors - Low, Choo Chin (Penerbit Universiti Kebangsaan Malaysia, 2025)
The emergence and relevance of immigration contractors in Malaysia’s migration management challenge the role of intermediaries and agents. The engagement of immigration services marked a substantial transformation in the state’s migration management by eliminating independent agents, whom the state could not effectively supervise, and substituting them with a few immigration contractors. In 2015, the state outsourced digital visa management to an information technology developer and in 2016, the state appointed private immigration contractors to manage the state’s regularisation activities. The emergence of state contractors raised a few questions: What factors explain the rise of immigration contractors? What are the implications of this rise for Malaysia’s migration governance? The analysis draws from official documents, company media statements, civil society press releases, news media, and secondary literature. There are two research findings. First, the emergence of immigration contractors can be seen as centralising immigration functions and addressing the mismanagement of individual agents, discouraging profiteering, eliminating fake agents, and protecting migrant rights. Second, instead of playing the active role of gatekeepers, private immigration contractors in the Malaysian context engage in a passive administrative role as they carry out the government’s directives and do not exercise autonomy in their decision-making. This differs from the literature on outsourcing and privatisation, which demonstrated how the involvement of private actors in migration alters the processes by extending and changing the character of state power.